The Song of King Gesar as Narrative Space: Translating Epic Narrative into Cultural Landscape - Chen, Xiaoyu (Asia Pacific Economic and Management Review, 2026)
As a living epic sustained primarily through oral transmission The Song of King Gesar has increasingly entered contemporary public culture through spatial and material forms. Taking The Song of King Gesar as a case study, this article investigates how epic narrative is translated from a linguistic and performative mode into a spatial and experiential cultural landscape. Drawing on spatial narratology and cultural landscape theory, the study examines the narrative characteristics of The Song of King Gesar, the logic through which temporal narrative structures are transformed into spatial configurations, and the concrete spatial practices through which this translation is realized. The analysis demonstrates that The Song of King Gesar is not a simple visualization or display of epic content, but a form of narrative space constructed through spatial layout, symbolic nodes, and visitor pathways. In this process, core epic motifs are re-encoded as spatial symbols, while narrative progression is achieved through embodied movement and experiential engagement, reshaping both the mode of representation and the mode of reception. By shifting the epic from a tradition centered on telling and listening to a cultural practice structured around seeing, walking, and experiencing, this spatial translation enables the epic to sustain its core cultural meanings while acquiring new forms of visibility and continuity in contemporary society. This study contributes to research on living epics and intangible cultural heritage by demonstrating how traditional narratives can be rearticulated through cultural landscapes, thereby offering a spatial perspective on the contemporary transformation of narrative tradition.